Association between PM2.5-bound metals and pediatric respiratory health in Guangzhou: An ecological study investigating source, health risk, and effect - Zheng, Yi; Chen, Sili; Chen, Yuyang; Li, Jingye; Xu, Binhe; Shi, Tongxing; Yang, Qiaoyuan (Frontiers in Public Health, 2023)
Background: The adverse effects of 2.5-µm particulate matter (PM2.5) exposure on public health have become an increasing concern worldwide. However, epidemiological findings on the effects of PM2.5-bound metals on children’s respiratory health are limited and inconsistent because PM2.5 is a complicated mixture. Objectives: Given the vulnerability of children's respiratory system, aim to pediatric respiratory health, this study evaluated the potential sources, health risks, and acute health effects of ambient PM2.5-bound metals among children in Guangzhou, China from January 2017 to December 2019. Methods: Potential sources of PM2.5-bound metals were detected using positive matrix factorization. A health risk assessment was conducted to investigate the inhalation risk of PM2.5-bound metals in children. The associations between PM2.5-bound metals and pediatric respiratory outpatient visits were examined with a quasi-Poisson generalized additive model (GAM). Results: During 2017-2019, the daily mean concentrations of PM2.5 was 53.39 μg/m3, and the daily mean concentrations of PM2.5-bound metals range 0.03 ng/m3 (thorium [Th] and beryllium [Be]) from to 396.40 ng/m3 (iron [Fe]). PM2.5-bound metals were mainly contributed by motor vehicles and street dust. PM2.5-bound arsenic (As), cadmium (Cd), cobalt (Co), chromium (Cr)(VI), nickel (Ni), and lead (Pb) were found to pose a carcinogenic risk. A quasi-Poisson GAM was constructed that showed there were significant associations between PM2.5 concentrations and pediatric outpatient visits for respiratory diseases. PM2.5 was significantly associated with pediatric outpatient visits for respiratory diseases. Moreover, with a 10 µg/m3 increase in Ni, Cr(VI), Ni, and As concentrations, the corresponding pediatric outpatient visits for respiratory diseases increased by 2.89% (95% CI: 2.28–3.50%), acute upper respiratory infections increased by 2.74% (2.13–3.35%), influenza and pneumonia increased by 23.36% (20.09–26.72%), and acute lower respiratory infections increased by 16.86% (15.16–18.60%), respectively. Conclusions: Our findings showed that PM2.5 and PM2.5-bound As, Cd, Co, Cr(VI), Ni, and Pb had adverse effects on pediatric respiratory health during the study period. New strategies are required to decrease the production of PM2.5 and PM2.5-bound metals by motor vehicles and to reduce levels of street dust to reduce children’s exposure to these pollutants and thereby increase child health.